Elektroniczna wymiana danych XML/EDI w sprawozdawczości finansowej i rozliczeniach podatkowych - Fliegner, Wojciech (Electronic data interchange XML/EDI in financial reporting and tax collection, 2006)
The creation, analysis, and verification of financial reports is time-consuming and error-prone. Data must be manually re-entered or copied and pasted. Extensible Business Reporting Language (XBRL) alleviates much of this pain by attaching “bar codes” to individual pieces of data within documents and spreadsheets so this information can be automatically pulled into reports and analyzed. In this paper we focus also on submission of electronic tax forms.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 187-195